ETUDE PHYTOCHIMIQUE ET BIOLOGIQUE DE THYMUS ALGERIENSIS - ABIDI Nihal; BARKAT Ouissal (My University, 2026)
This study focuses on the phytochemical and biological investigation of Thymus algeriensis, a medicinal and aromatic plant widely used in traditional medicine. The main objective was to evaluate its richness in phenolic compounds and to assess its antioxidant and antibacterial activities. Aqueous (decoction) and ethanolic (maceration) extracts were prepared from the aerial parts of the plant. Phytochemical analysis was carried out to determine the content of total phenolics, flavonoids, tannins, flavonols, and anthocyanins using standard spectrophotometric methods. The antioxidant activity of the extracts was evaluated using DPPH, ABTS, and FRAP assays. The results indicated that both extracts exhibited significant antioxidant activity in a concentration-dependent manner. However, the ethanolic extract showed higher effectiveness, which may be attributed to the better solubility and extraction of bioactive compounds in ethanol. In addition, the antibacterial activity was assessed using the disk diffusion method against three pathogenic bacterial strains: Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The findings revealed varying degrees of inhibition depending on the bacterial strain and the type of extract used. The results suggest that Thymus algeriensis is a promising natural source of bioactive compounds with potent antioxidant and antimicrobial properties. These findings support its potential application in pharmaceutical, food, and cosmetic fields. Nevertheless, further in vivo studies and toxicity evaluations are required to confirm its safety and effectiveness --------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- تهدف هذه الدراسة إلى تقييم الخصائص الكيميائية الحيوية والبيولوجية لنباتalgeriensis Thymus، وهو نبات عطري وطبي يستعمل على نطاق واسع في الطب التقليدي. تمحور الهدف الرئيسي حول تحديد محتواه من المركبات الفينولية ودراسة نشاطه المضاد للأكسدة والمضاد للبكتيريا. تم تحضير مستخلصين من الأجزاء الهوائية للنبات، مستخلص مائي بطريقة الغلي (Décoction) ومستخلص كحولي بطريقة النقع (Macération). وقد تم تحديد محتوى المركبات الفينولية الكلية، الفلافونويدات، التانينات، الفلافونولات والأنثوسيانينات باستعمال طرق طيفية قياسية. أظهرت نتائج اختبارات النشاط المضاد للأكسدةDPPH، ABTS، FRAPأن كلا المستخلصين يمتلكان قدرة معتبرة على تثبيط الجذور الحرة، مع تفوق واضح للمستخلص الكحولي، ويرجع ذلك إلى فعالية الإيثانول في استخلاص المركبات النشطة. كما تم تقييم النشاط المضاد للبكتيريا باستخدام طريقة الانتشار على الوسط الصلب ضد ثلاث سلالات بكتيرية ممرضة هيaureus Staphylococcus، Escherichia coliو aeruginosa Pseudomonasوقد أظهرت النتائج وجود تأثير مثبط متفاوت حسب نوع السلالة ونوع المستخلص. في الختام، تؤكد هذه الدراسة أن نبات algeriensis Thymus يمثل مصدراً طبيعياً واعداً للمركبات النشطة بيولوجياً ذات الخصائص المضادة للأكسدة والمضادة للميكروبات، مما يجعله قابلًا للاستعمال في مجالات متعددة، مع ضرورة إجراء دراسات إضافية للتأكد من فعاليته وسلامته. --------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------- Ce travail a porté sur l’étude phytochimique et biologique de Thymus algeriensis, une plante aromatique et médicinale largement utilisée en médecine traditionnelle. L’objectif principal était d’évaluer la richesse de cette plante en composés phénoliques ainsi que ses activités antioxydante et antibactérienne. Deux types d’extraits ont été préparés à partir des parties aériennes de la plante : un extrait aqueux obtenu par décoction et un extrait éthanolique obtenu par macération. La caractérisation phytochimique a permis de déterminer les teneurs en polyphénols totaux, flavonoïdes, tanins, flavonols et anthocyanes en utilisant des méthodes spectrophotométriques standards. Les activités antioxydantes ont été évaluées par les tests DPPH, ABTS et FRAP. Les résultats ont montré que les deux extraits possèdent une activité antioxydante significative, dépendante de la concentration, avec une efficacité plus marquée pour l’extrait éthanolique, ce qui pourrait être lié à une meilleure extraction des composés bioactifs. Par ailleurs, l’activité antibactérienne a été étudiée par la méthode de diffusion sur gélose vis-à-vis de trois souches bactériennes pathogènes : Staphylococcus aureus, Escherichia coli et Pseudomonas aeruginosa. Les résultats ont révélé une sensibilité variable des souches, traduisant un effet inhibiteur des extraits. Les résultats obtenus confirment le potentiel de Thymus algeriensis comme source naturelle de composés bioactifs possédant des propriétés antioxydantes et antimicrobiennes. Cette plante pourrait constituer une alternative intéressante aux substances synthétiques, bien que des études complémentaires soient nécessaires pour approfondir ses applications.
Keywords: algeriensis thymus، المركبات الفينولية، النشاط المضاد للاكسدة، النشاط المضاد للبكتيريا، المستخلصات النباتية; Thymus algeriensis; phenolic compounds; antioxidant activity; antibacterial activity; plant extracts.; composés phénolique; activité antioxydante; activité anti bactériennes; extraits végétaux.